Perceptions of parental marital conflict, experience of stress and coping mechanisms among adolescent daughters in an urban setting - Belen, Marinella Regina S.; De Leon, Maria Perlita E. (Quezon City College of Home Economics, University of the Philippines Diliman, 2013)
ABSTRACT This undergraduate thesis is about the perception, stress experienced, and coping mechanisms of adolescent daughters in the urban setting of Metro Manila whose parents are currently undergoing marital discord. It is a qualitative research that interviewed 20 female respondents, ages sixteen (16) to eighteen (18), who lived in Parañaque, Muntinlupa, Taguig, and Quezon City. The study described the perceptions of adolescent daughters regarding parental marital conflict. It identified the stresses they experienced because of it. And given the perceptions and stress related to parental marital discord, the corresponding coping mechanisms adolescent daughters are developed. When the perception and stress they experience is largely negative, their resulting coping mechanism tends to be maladaptive, causing harm to themselves or others. But when either the perception of the conflict or the stress experienced is considered to be neutral or positive in nature, they utilize behaviors that allow them to cope appropriately with the family crisis. With further research, the findings of this study can be further developed to help all children whose families have parents who are in frequent and/or hostile conflict with one another.
Thesis (BSFLCD)--University of the Philippines Diliman.
Keywords: Teenage girls -- Philippines; Parent and teenager -- Philippines